Change in size-at-maturity of the yellownose skate Dipturus chilensis (Guichenot, 1848) (Elasmobranchii: Rajidae) in the SW Atlantic - Paesch, Laura; Oddone, María C. [UNESP] (Sociedade Brasileira de Ictiologia, 2008)
Um total de 3518 espécimes (1607 machos e 1911 fêmeas) de Dipturus chilensis foi amostrado. Os machos tiveram comprimentos totais entre 44.0 e 99.0 cm e as fêmeas entre 45.0 e 110.0 cm. A composição de comprimentos totais das capturas agrupadas foi significativamente diferente entre ambos os sexos, sendo as fêmeas maiores do que os machos. A razão sexual favoreceu as fêmeas. O comprimento total em que 50% dos espécimes foram retidos pelo aparelho de pesca foi de 69.0 cm nos machos e de 73.0 cm nas fêmeas. Uma sub-amostra de 124 espécimes (48 machos e 76 fêmeas) foi analisada para avaliação dos parâmetros reprodutivos. Para os machos, o tamanho de 50% de maturidade resultou em 78.5 cm enquanto que para as fêmeas este parâmetro foi estimado em 81.4 cm. Observações preliminares sobre a descrição da cápsula ovígera são também fornecidas.

A total of 3518 specimens (1607 males, 1911 females) of Dipturus chilensis were sampled. Males ranged from 44.0 to 99.0 cm and females from 45.0 to 110.0 cm. Total length composition of the grouped catches differed significantly among sexes, with females being larger than males. The sex ratio favored the females. The total length at which 50% of the specimens were retained by the gear was 69.0 cm for the males and 73.0 cm for the females. A sub-sample of 124 specimens (48 males, 76 females) was analyzed for reproductive assessment. For the males, size at 50% maturity was estimated at 78.5 cm, while for the females this parameter was estimated at 81.4 cm. Preliminary observations on the description of the egg capsules are also provided.
Keywords: Clasper; Fishery-dependent samples; Rajid; Reproduction; Size composition